The Role of Professor Abul Khair Nazmul Karim to the Emergence and Development of Sociology in Bangladesh: A Historical Analysis (Social Science Review, 2026)
Throughout history, various disciplines in different areas have emerged and developed through the work of numerous theorists, philosophers, and scholars. A few theorists and scholars, not all, contributed much more effectively, paving the way for the development of a new discipline. A. K. Nazmul Karim was one of them who was one of the founding fathers of Sociology in Bangladesh. This study pivotally focused on the role of A. K. Nazmul Karim in the emergence and development of Sociology in Bangladesh. An extensive historical analysis was conducted to examine the impacts of Karim’s direct and indirect activities, as a teacher and a sociologist, on the emergence and development of Sociology in Bangladesh. Results showed that, through the great efforts of Nazmul Karim and with the help of UNESCO, the Sociology department was established as a separate discipline at the University of Dhaka in the 1957-58 academic session. Karim’s contribution to developing academic curriculum, conducting research and publication, providing inspiration and guidelines to practice sociological study, engaging students with empirical research, arranging and participating in seminars, symposiums, and conferences, as well as circulating sociology discourse at university and college levels, has paved the way for the growth of Sociology discourse across Bangladesh. The findings of this study would provide important guidelines for students, teachers, and researchers in Bangladesh to explore and apply sociological knowledge.Social Science Review [The Dhaka University Studies, Part-D], Vol. 42, No.2, December 2025, pp. 159-185